Insektosemityzm - Żółkoś, Monika (Narracje o Zagładzie [czasopismo zamknięte], 2017)
Insecto‑Semitism This article is an attempt at describing Nazi anti‑Semitic narrations from the animal studies perspective. The author traces the ways of using cultural images of insects in persecutory discourses, which by means of the “animalism” category not only degrade the Jewish identity, but also deprive it of human subjectivity. The article shows the creation of the specific interpretation of Semitic corporeality – presented as budding and expanding, and simultaneously repulsive and estranging – by means of insect metaphors. What seems to be particularly interesting is tracing the movement of anti‑Semitic connotations, which link the Jewish identity with more and more lowly and non‑human living forms – insects, parasites, and bacteria. Their impact on the collective consciousness leads from the metaphor to that which is made extremely literal, whose culminations are ghettoes and death camps. Literary endeavours to oppose the degrading images connecting the Jewish community with the negatively valorised animality provide yet another important thread of the article. The author examines various strategies of discursive resistance, found in Marian Pankowski’s pieces and in Julian Tuwim’s poem. Their common ground is not so much rejecting Nazi similes, presenting the Jews as equal with insects, as appropriating these images and filling them with new content, which turns out to be a more sophisticated form of subversion. Key words: animal studies, non‑anthropocentric humanities, animals, insects, Jews, anti-Semitism, persecutory strategies, symbolic violence